Attributes of successful public participation in planning for sustainable tourism in protected areas: a modified Delphi study - Abdul Gani, Arni; Awang, Khairil Wahidin; Mohamad, Abdullah; Samdin, Zaiton (Universiti Putra Malaysia Press, 2015)
Tourism in protected areas has developed and is becoming desirable attractions in many parts of the world. The expanding of the industry into the fragile and sensitive areas necessitates proper planning and management to ensure balance in development and protection of the environment. Sustainable development has become the buzz word in planning. One important principle of sustainable development is to encourage true participation of the public in planning and decision making. In this study, a modified Delphi technique was introduced to determine whether an informed group of experts in protected area management could arrive at a consensus regarding the important attributes of a successful public participation. Three expert groups representing government agencies, nongovernmental agencies, and academics in Malaysia were presented with a questionnaire containing 30 attributes in two dimensions perceived as being the important dimensions in determining a successful public participation. The contributions of individuals via this tool produced group perspective not otherwise attainable. The results from the Delphi rounds confirmed a consensus of opinion between the three categories of experts with an introduction of new attributes deemed important with reference specifically to Malaysia.